Analisis Model Kepuasan terhadap Pembelian Ulang - Farida, Naili (Department of Management, Faculty of Economics, Universitas Negeri Semarang, 2014)
The objective of the research was to test the influence of brand equity, customer value and lifestyle which were mediated by consumer satisfaction toward re-purchasing of gadget products in Semarang. The respondents of the study were all consumers who have purchased Samsung gadget products. It was a purposive sampling study with 120 respondents. The data were analyzed by Partial Least Square (PLS). The result of the study showed that there was an influence of brand equity toward satisfaction, but in the lifestyle context and customer value did not give any influence toward satisfaction. Whereas; the satisfaction gave influence toward re-purchase. It is expected that this study can increase the repurchasethrough brand equity, lifestyle and customer values in the satisfaction context.